Peroxisome-targeted and tandem repeat multimer expressions of human antimicrobial peptide LL37 in Pichia pastoris. Issue 3 (16th March 2017) - Xiao, Siwei; Gao, Yanyun; Wang, Xiaolong; Shen, Wei; Wang, Jinjia; Zhou, Xiangshan; Cai, Menghao; Zhang, Yuanxing
ABSTRACT: Although the human antimicrobial peptide LL37 has a broad spectrum of antimicrobial activities, it easily damages host cells following heterologous expressions. This study attempted two strategies to alleviate its damage to host cells when expressed in Pichia pastoris using the AOX1 promoter. Tandem repeat multimers of LL37 were first designed, and secretion expression strains GS115-9K-(DPLL37DP) n ( n = 2, 4, 6 and 8) containing different copies of the LL37 gene were constructed. However, LL37 tandems still killed the cells after 96 hr of induction. Subsequently, peroxisome-targeted expression was performed by adding a peroxisomal targeting signal 1 (SKL) at the C-terminus of LL37. The LL37 expression strain GS115-3.5K-LL37-SKL showed no significant inhibition in the cells after induction. Antibacterial activity assays showed that the recombinant LL37 expressed in peroxisomes had good antimicrobial activities. Then, a strain GS115-3.5K-LL37-GFP-SKL producing LL37, green fluorescent protein, and SKL fusion proteins was constructed, and the fusion protein was confirmed to be targeting the peroxisomes. However, protein extraction analysis indicated that most of the fusion proteins were still located in the cell debris after cell disruption, and further studies are required to extract more proteins from the peroxisome membrane.